Germination effect of soybean cv. BR-13 and Paraná on phitic acid, total P and trypsin inhibitors levels - Ribeiro, Mara Lucia Luiz; Ida, Elza Iouko; Oliveira, Maria Cristina Neves de (Pesquisa Agropecuaria Brasileira, 1999)
The aim of this work was to evaluate the effect of germination on the antinutritional constituents of soybean, phytic acid, total P and trypsin inhibitors that interfere with the utilization of proteins and other substances. The decrease of the nutrient utilization results in growth inhibition, hypoglycemia or damage to animal tissues. Seeds of soybean (Glycine max (L.) Merrill) cultivars BR-13 and Paraná were incubated in germination chamber at 25°C and 100% of humidity, from 0 to 72 hours, and samples were collected in intervals of six hours. The Paraná cultivar presented higher amount of phytic acid, total phosphorus and trypsin inhibitors, than the BR-13 cultivar. The analysis of variance and comparison among the means indicated that, in 72 hours of germination, there was a significant increase (p < 0.05) on the amount of total phosphorus (8.5% and 3.6% for BR-13 and Paraná cultivars, respectively) and on the level of trypsin inhibitors (22.05% and 17.10% for BR-13 and Paraná cultivars, respectively) while the amount of phytic acid decreased 15.96% and 9.46% for BR-13 and Paraná cultivars, respectively.